Productive efficiency of beef cattle production in Botswana: a latent class stochastic meta-frontier analysis - Bahta, Sirak; Temoso, Omphile; Ng'ombe, John N.; Rich, Karl M.; Baker, Derek; Kaitibie, Simeon; Malope, Patrick (Frontiers Media, 2023)
Efficiency in food production is crucial for sustainable agriculture in developing countries. This paper contributes to the existing literature by presenting an innovative approach to modeling productive efficiency in beef cattle production. Treating farm performance across regions as unobserved heterogeneity, we determine technical efficiency of beef cattle production in Botswana. We aim to shed light on the factors influencing efficiency in this sector.The study utilized block-level data from various annual agricultural surveys (2006–2014) covering 26 agricultural districts and six agro-ecological regions in Botswana. We employed a latent class stochastic frontier model complemented with the stochastic meta-frontier analysis.Results show that the best performing farming systems in terms of efficiency are districts with well-developed infrastructure and better access to output and input markets. In contrast, the farming systems that perform poorly consist of agricultural districts without access to livestock advisory centers, with higher average temperatures and foot and mouth disease, limiting access to export markets. The mean technical efficiency scores for beef production for agricultural districts in class one and two were 62 and 59%, respectively, implying high potential to improve beef production using the same level of agricultural inputs through efficiency-enhancing investments.Based on our results, it is crucial for agricultural policies to prioritize regionally specific investments that address the needs of the under-performing districts. By targeting the lagging districts, policymakers can help beef producers improve their input efficiency and bridge the technological gaps to the meta-frontier. This can be achieved through investments in infrastructure, access to livestock advisory services, and disease control measures. Such efforts will not only enhance the efficiency of beef production but also contribute to the overall sustainability of the agricultural sector in Botswana.